KREASI VAS TERAKOTA UNTUK UNTUK MENDUKUNG ESTETIKA DESA WISATA PADUSAN MOJOKERTO PROGRAM KEMITRAAN WILAYAH KAMPUS UM - ponimin, Ponimin; Wardana, Mitra Istiar; Hadi, Nur; Nusantari, Okta Viviana Asmi (Universitas Mataram, 2025)
Padusan Pacet Mojokerto Village has pioneered the development of a tourism village based on natural and cultural environments. The tourism village managers realize that to innovate in the region requires technical knowledge and experience. The creative art team from fine arts lecturers at Malang State University who are members of the community service program, have solved the problem, through a regional partnership program. Namely by creating visual icons created from sources of ideas for cultural artifacts from the Majapahit era. In order to strengthen these creations, they also strengthen the visual image of the Padusan tourism village. To achieve this, creative art methods are needed, including: (a.) Planning a terracotta vase creation program by the UM campus creative team together with the Padusan tourism village management team regarding the formulation of the terracotta vase product concept, (b.) The creative process of designing terracotta vase design drawings (c.) The process of production and display of terracotta vase creations. (d.) Analysis of the creative results of the exterior terracotta vases of the Padusan tourism village.